2019
DOI: 10.1016/j.neo.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

MCM2, MCM4, and MCM6 in Breast Cancer: Clinical Utility in Diagnosis and Prognosis

Abstract: Breast cancer is a heterogeneous disease comprising the estrogen receptor (ER)–positive luminal subtype which is subdivided into luminal A and luminal B and ER-negative breast cancer which includes the triple-negative subtype. This study has four aims: 1) to examine whether Minichromosome Maintenance (MCM)2, MCM4, and MCM6 can be used as markers to differentiate between luminal A and luminal B subtypes; 2) to study whether MCM2, MCM4, and MCM6 are highly expressed in triple-negative breast cancer, as there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 61 publications
5
66
0
Order By: Relevance
“…MCM6, a component of minichromosome maintenance (MCM) protein complex, functions to initiate DNA replication and unwinding based on its replicative helicase activity. It has been demonstrated that the overexpression of MCM6 can promote tumorigenesis, [ 31 ] also seen in the present study. Further study is needed to identify how DNA methylation regulated MCM6 expression to affect the development of RB.…”
Section: Discussionsupporting
confidence: 88%
“…MCM6, a component of minichromosome maintenance (MCM) protein complex, functions to initiate DNA replication and unwinding based on its replicative helicase activity. It has been demonstrated that the overexpression of MCM6 can promote tumorigenesis, [ 31 ] also seen in the present study. Further study is needed to identify how DNA methylation regulated MCM6 expression to affect the development of RB.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, CHEK1 was co-expressed with minichromosome maintenance complex component (MCM family) and flap eendonuclease 1 (FEN1) expressed in colorectal cancer. The MCM family (MCMs) has been reported to be associated with numerous cancer types [35][36][37], such as the promotion of metastasis of liver cancer through the Mitogen-activated protein kinase kinase(MEK)/ extracellular signal-regulated kinases (ERK) pathway (MCM6) [38], as a prognostic factor in patients with lung squamous cell carcinoma [39]. Many studies indicate the central roles of MCMs in genome stability, including the regulation of transcription, chromatin remodeling, and checkpoint responses [40][41][42].…”
Section: Co-expression Profile Of Chek1 In Colorectal Cancermentioning
confidence: 99%
“…Besides, extent of HMGA1 phosphorylation has been found to be differentially expressed in response to MCM2 perturbation and has a significant role to play in modulating cell behaviors of lung cancer cells [ 17 ]. MCM2 also has wide clinical application value in breast cancer diagnosis and prognosis [ 18 ]. Of note, MCM2 has been proved to be closely related to stem cells.…”
Section: Introductionmentioning
confidence: 99%